Principals as Literacy Leaders with Indigenous Communities (PALLIC) building relationships: one school's quest to raise Indigenous learners' literacy. Issue 2 (2nd April 2016) - Riley, Tasha; Webster, Amanda
Abstract : In 2011 to 2012, 48 schools in the Northern Territory, South Australia and Queensland participated in the Principals as Literacy Leaders with Indigenous Communities (PALLIC) project. Central to this project was the establishment of positive working relationships between school principals and Indigenous community leaders in order to improve Indigenous literacy rates. Professional development in leadership skills and effective literacy instruction was provided through five professional learning modules. Participants worked together to create an action plan to support the literacy achievement of Indigenous students in their schools and communities. This article presents a case study of one participating school in Northern Queensland that successfully utilised the PALLIC framework to facilitate leadership actions and activities between Indigenous community and school leaders in order to form productive partnerships for the teaching of reading. In particular, the case study highlights the way that school leaders and Indigenous leaders established shared leadership and shared ways of learning in the school for reading outcomes of Indigenous students.